2008
DOI: 10.1128/jvi.01803-07
|View full text |Cite
|
Sign up to set email alerts
|

Dominant-Negative FADD Rescues the In Vivo Fitness of a Cytomegalovirus Lacking an Antiapoptotic Viral Gene

Abstract: Genes that inhibit apoptosis have been described for many DNA viruses. Herpesviruses often contain even more than one gene to control cell death. Apoptosis inhibition by viral genes is postulated to contribute to viral fitness, although a formal proof is pending. To address this question, we studied the mouse cytomegalovirus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
97
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(103 citation statements)
references
References 49 publications
6
97
0
Order By: Relevance
“…While M36 is thought to inhibit caspase-8 activation by binding to procaspase 8 (20,21), MC159 is thought to exert its inhibitory effect primarily by binding to FADD and preventing recruitment of procaspase 8 to the death-inducing signaling complex (DISC) (51) or oligomerization of the DISC (52). Remarkably, a previous study has shown that the loss of M36 is almost completely rescued by dominant negative FADD, which was overexpressed by using a strong heterologous promoter (24). Our results suggest that the inhibitory activity of MC159 or its expression level is insufficient for a complete reversal of the ⌬M36 phenotype in infected macrophages.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…While M36 is thought to inhibit caspase-8 activation by binding to procaspase 8 (20,21), MC159 is thought to exert its inhibitory effect primarily by binding to FADD and preventing recruitment of procaspase 8 to the death-inducing signaling complex (DISC) (51) or oligomerization of the DISC (52). Remarkably, a previous study has shown that the loss of M36 is almost completely rescued by dominant negative FADD, which was overexpressed by using a strong heterologous promoter (24). Our results suggest that the inhibitory activity of MC159 or its expression level is insufficient for a complete reversal of the ⌬M36 phenotype in infected macrophages.…”
Section: Discussionmentioning
confidence: 60%
“…It is also conceivable that M36 has an additional function (besides inhibiting death receptor-dependent apoptosis) not shared by MC159. This hypothesis, however, seems unlikely, as dominant negative FADD rescued the replication defect in macrophages (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, m38.5 provides the function of the unrelated HCMV UL37 exon 1 (UL37x1) (9, 51) while, on the other hand, UL45 lacks the M45-encoded protein-protein interaction domain required to inhibit cell death signaling of receptor-interacting proteins (RIP) (89, 90). Evidence thus far indicates that the CMV-common gene products M36 and UL36 prevent cell death by a conserved mechanism (51,54,57,73), prompting the current evaluation of UL36 in differentiated macrophages.M36-deficient viruses are severely debilitated in vivo and induce apoptosis of tissue macrophages (17,18). In vitro studies indicated that M36-deficient virus replicates in fibroblasts or endothelial cells but not macrophage cell lines (57), results that may contribute to replication in some organs of the in-* Corresponding author.…”
mentioning
confidence: 99%